2021
DOI: 10.3389/fpsyg.2021.643977
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Impact of Quarantine on Loneliness, Death Obsession, and Preoccupation With God: Predictors of Increased Fear of COVID-19

Abstract: Most countries are facing the societal challenging need for a new quarantine period due to the increasing number of COVID-19 infections, indicating a second or even third wave of disease. The COVID-19 pandemic has brought to the surface existential issues that are typically less present in people's focal attention. The first aim of this study was to identify some of these existential struggles such as increased feelings of loneliness, death obsession, and preoccupation with God. Secondly, we explored the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 64 publications
4
32
1
Order By: Relevance
“…The data obtained indicates the discrepancy between certain measures imposed by the authorities and the desires of the population, a discrepancy that can lead to social ruptures and behavioral deviations, as suggested in Enea's study [12].…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The data obtained indicates the discrepancy between certain measures imposed by the authorities and the desires of the population, a discrepancy that can lead to social ruptures and behavioral deviations, as suggested in Enea's study [12].…”
Section: Discussionmentioning
confidence: 50%
“…Women expressed a greater fear than men [9]. Another study showed that after an average isolation time of almost 37 days, the perceived levels of loneliness, death obsession, and preoccupation with God significantly increased in the Romanian sample [12]. Also, when loneliness levels are high, age becomes a significant predictor of fear of COVID-19 because the elderly are more afraid than younger people when they feel lonely.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It was found that there was no boredom amongst physically active subjects, and they reported less fear of coronavirus disease [ 39 ]. In addition, predictors of fear included gender and the knowledge of the person diagnosed with coronavirus disease, while days spent in isolation were not a predictor of fear of the coronavirus disease, nor were they associated with feelings of loneliness [ 44 ]. Higher levels of depression, general anxiety, and insomnia were found in nurses compared with medical assistants and physicians, while physicians and health workers in COVID units showed greater coping skills.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Romania, which included 1340 adult respondents during the pandemic itself, confirmed the existential issues raised by the coronavirus disease pandemic. It identified an increase in feelings of loneliness, obsession with death, and preoccupation with God during quarantine, which also predicted fear of the coronavirus [ 44 ].…”
Section: Introductionmentioning
confidence: 99%